Potential of Fables as Learning Resources for Environmental Education and Its Relevance to the Merdeka Belajar Curriculum - Holy Ichda Wahyuni; Agus Budiman; Ratno Abidin; Elmi Tri Yuliandari (Jurnal Pendidikan Indonesia Gemilang, 2023)
The development of noble character, especially the awareness of protecting the environment, can be optimized through the internalization process in learning. Children's literary media is an effective medium, especially applied to elementary school-aged children at the golden age of character planting. Stories in children's literature can dialogue life in an interesting, concrete, and contextual way. The fable entitled "The Story of a Seagull and the Cat Who Teaches It to Fly" by Luis Sepulveda is one of the translated fables with the theme of environment and family, which is considered to have the potential to be used as a learning resource for environmental education. Research that attempts to analyze the environment's value in fables and its use as a learning resource in the era of the MerdekaBelajar(independent learning) curriculum is still very limited. This research aimed to; 1) describe the value of environmental education in the fable "The Story of a Seagull and the Cat Who Teaches It to Fly" by Luis Sepulveda; 2) describe the use of fables as a learning resource for elementary school students; 3) describe its relevance to the profile of Pancasila students in the independent learning curriculum. This research is qualitative, using a text study approach and descriptive analysis. This study showed that this fable can be used as a source of learning materials for elementary school students following the theories that support student development and learning approaches, such as; meaningful learning and constructivism, as well as relevant to the proclamation of the Pancasila student profile in the Merdeka Belajar(independent learning) curriculum. The implication of this study is a recommendation for developing children's literature-based learning media to internalize environmental awareness characters